'Candidatus Chloroploca mongolica' sp. nov. a new mesophilic filamentous anoxygenic phototrophic bacterium. Issue 16 (14th August 2021) - Bryantseva, Irina A; Grouzdev, Denis S; Krutkina, Maria S; Ashikhmin, Aleksandr A; Kostrikina, Nadezda A; Koziaeva, Veronika V; Gorlenko, Vladimir M
ABSTRACT: A mesophilic filamentous anoxygenic phototrophic bacterium, designated M50-1, was isolated from a microbial mat of the Chukhyn Nur soda lake (northeastern Mongolia) with salinity of 5−14 g/L and pH 8.0−9.3. The organism is a strictly anaerobic phototrophic bacterium, which required sulfide for phototrophic growth. The cells formed short undulate trichomes surrounded by a thin sheath and containing gas vesicles. Motility of the trichomes was not observed. The cells contained chlorosomes. The antenna pigments were bacteriochlorophyll d and β- and γ-carotenes. Analysis of the genome assembled from the metagenome of the enrichment culture revealed all the enzymes of the 3-hydroxypropionate bi-cycle for autotrophic CO2 assimilation. The genome also contained the genes encoding a type IV sulfide:quinone oxidoreductase ( sqrX ). The organism had no nifHDBK genes, encoding the proteins of the nitrogenase complex responsible for dinitrogen fixation. The DNA G + C content was 58.6%. The values for in silico DNA‒DNA hybridization and average nucleotide identity between M50-1 and a closely related bacterium ' Ca . Chloroploca asiatica' B7-9 containing bacteriochlorophyll c were 53.4% and 94.0%, respectively, which corresponds to interspecies differences. Classification of the filamentous anoxygenic phototrophic bacterium M50-1 as a new ' Ca . Chloroploca' species was proposed, with the species name ' Candidatus Chloroploca mongolica' sp. nov. Abstract : We present the description of a novel mesophilic phototrophic Chloroflexota bacterium from a Mongolian soda lake